Les mutations des politiques de déplacement dans les villes moyennes : des ambitions aux contraintes de l’action. L’exemple de Périgueux - Emilie Roudier (Belgeo)
This paper analyses the mutations of mobility policies in French mid-sized cities since the 2000s. It studies the case of Périgueux, a mid-sized city in Dordogne, and its inter-municipal transport policies. It proposes to analyze these mutations through the prism of the Périgueux interchange train station project, a major project of the inter-municipality. Through a study of the launch and design of this project, the article shows paradigmatic shifts in local policies and political, technical and financial implementation constraints. This case study is an opportunity to question mobility and transport in mid-sized cities. It puts in perspective local issues, evolutions of frameworks and practices and the limits of local authorities capacity for action.